What Happens to the Immune Microenvironment After PD-1 Inhibitor Therapy? - Wang, Qingyi; Xie, Bin; Liu, Shuang; Shi, Ying; Tao, Yongguang; Xiao, Desheng; Wang, Wenxiang (Frontiers in Immunology, 2021)
The fruitful results of tumor immunotherapy establish its indispensable status in the regulation of the tumorous immune context. It seems that the treatment of programmed cell death receptor 1 (PD-1) blockade is one of the most promising approaches for cancer control. Significant efficacy of PD-1 inhibitor therapy has been made in several cancer types, such as breast cancer, lung cancer, and multiple myeloma. Even so, the mechanisms of how anti-PD-1 therapy takes effect by impacting the immune microenvironment and how partial patients acquire the resistance to PD-1 blockade have yet to be studied. In this review, we discuss the crosstalk between immune cells and how they promote PD-1 blockade efficacy. In addition, we also depict factors that may underlie tumor resistance to PD-1 blockade and feasible solutions in combination with it.